In vitro studies on Bothrops venoms cytotoxic effect on tumor cells - Jorge, Roberta J. B.; Martins, Alice M. C.; Morais, Isabel C. O.; Ximenes, Rafael M.; Rodrigues, Felipe A. R.; Soares, Bruno M.; Evangelista, Janaina S. A. M.; Toyama, Marcos H. [UNESP]; Martins, Aline M. A.; Moraes Filho, Manoel O.; Monteiro, Helena S. A. (My University, 2011)
Background: Animal venoms are complex mixtures of proteins and non proteins components with several biological activities. Snake venoms represent an essentially unexplored source of bioactive compounds that may cure disease conditions which do not respond to currently available therapies. These venoms possess many pharmacological activities, as cytotoxic and/or lytic effects on tumor cells in vitro. Herein, were investigated the in vitro cytotoxicity of three Bothrops venoms in tumor cell lines. Methods: Cytotoxic effect was evaluated in HCT-8 (colon - human), SF-295 (nervous system - human), HL-60 (human leukemia) and MDAMB-435 (breast - human). Cell density and membrane integrity were determined by the exclusion of propidium iodide. To determine whether Bothrops venoms treated cells were undergoing an apoptotic and/ or necrosis death, phosphatidylserine (PS) externalization was measured after the incubation with the venom. Results: Botrhops venons showed significant cytotox- city against all cell lines in study. Cell density and membrane integrity were determined by the exclusion of propidium iodide. The Bothrops venoms reduced the cell number and revealed the presence of a necrotic population when the cells was exposed to the B. pauloensis B. diporus and B. pirajai venoms. To determine whether Bothrops venoms treated cells were undergoing an apoptotic and/or necrosis death, PS externalization was measured after the incubation with the venom and it was observed necrotic and apoptotic cells. Conclusions: All Bothrops venoms tested showed cytotoxicity against tumor cell lines through inducing of necrosis and apoptosis. © 2011 Old City Publishing, Inc.
Keywords: Apoptosis; Bothrops venoms; Citotoxicity; Flow citometry; Necrosis; Tumor cells